ANALISIS KUALITAS DAN FASILITAS SWAARSIP WEB REPOSITORI INSTITUSI LEMBAGA PENELITIAN: PERBANDINGAN LIPI DAN LEMBAGA INTERNASIONAL - Yaniasih, Yaniasih; Ardiansyah, Firman; Basuki, Sulistyo (BACA: Jurnal Dokumentasi dan Informasi, 2015)
Many research organization have been developing institutional repositories (IRs) to increase their researches impact, but in Indonesia there is only one research organization’s IR i.e. Indonesian Institute of Sciences (Lembaga Ilmu Pengetahuan Indonesia/LIPI) Institutional Repository. Therefore, the study of this IRs is very important to encourage research organizations to develop their IRs. This study analyzed the quality and self-archiving facilities of LIPI and world best IRs website based on Webometrics ranking. The method used web analysis on content, features and policies. The result showed that best quality IRs has a mandatory regulations to deposit researcher’s scientific work as well as a clear policy on the type of content, copyrights, and access. These IRs also provide informative features and services to supporting researcher’s self-archiving as well as facilitating public to access the web.